Inteligência acadêmica como suporte à formulação de estratégias na gestão da pós-graduação stricto sensu em administração - Macedo, Daniela Luiza de (2008)
This study explores the contribution of a System of Academic Intelligence - SIAc as has supported to the formularization of strategies in the management of the one After Graduation Stricto Sensu in Administration, based on literature on Competitive Intelligence - IC. The objective of this study is to consider contributions to the implantation of a SIAc as it has supported to the formularization of strategies the Stricto Sensu Administration Programs, on the basis of the analysis of the current management of two Administration Programs selected, more specifically, to identify and to characterize the strategy of management of the UNINOVE and USP Stricto Sensu Administration Programs, according to perception of the social citizens keys, to identify the contributions of the IAc in the strategical management of these Programs and to consider contributions the implantation of a Academy Intelligence System - SIAc for supporting the management of Stricto Sensu Administration Programs. The results had indicated that in a general way, in the Programs do not have a structure of Academic Intelligence capable to generate specific strategies in extended stated periods more, making with that the Programs obtain to reach superior levels of quality to the current levels.